Proceso de atención de enfermería en paciente fumador habitual de 65 años con enfermedad obstructiva crónica. - Manobanda Coles, Byron Elias (2021)
Chronic obstructive pulmonary disease (COPD) is a preventable and treatable condition that makes it difficult for air to be expelled from the lungs. This difficulty in emptying the lungs (airflow obstruction) can cause shortness of breath or a feeling of tiredness due to the effort you make to breathe. COPD is a term that includes chronic bronchitis, emphysema, and a combination of the two. There are many factors that cause COPD, although the most common cause is cigarette smoke. Environmental factors and genetics can also cause this disease. Some common symptoms of COPD are shortness of breath, cough, and / or heavy mucus that does not go away, indicating the need for a breathing test called spirometry, which measures airway obstruction. The first and most important treatment for smoking patients is to stop smoking. The following case study and research was carried out using bibliographic sources on different conceptualizations about this pathology. For a clear and specific concept, and also to help understand the cause and take the correct care procedures. The interview, the collection of objective and subjective data were used as a research method, through evaluation as a physical examination and complementary examination, analysis and organization to identify problems that interfere with the patient's health.